2022
DOI: 10.48550/arxiv.2202.04085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Celestial Blocks and Transverse Spin in the Three-Point Energy Correlator

Abstract: Quantitative theoretical techniques for understanding the substructure of jets at the LHC enable new insights into the dynamics of QCD, and novel approaches to search for new physics. Recently, there has been a program to reformulate jet substructure in terms of correlation functions, E( n 1 )E( n 2 ) • • • E( n k ) , of light-ray operators, E( n), allowing the application of techniques developed in the study of Conformal Field Theories (CFTs). In this paper we further develop these techniques in the particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 161 publications
0
13
0
Order By: Relevance
“…In addition to the leading asymptotic behaviours we provide, our result contains information about subleading powers as well. The data in the triple-collinear, squeezed and coplanar limit will shed new light on corresponding OPE limits of the light-ray operators [64], thus making it possible to understand these limits at arbitrary coupling [65,66]. In the meantime, the analysis in each aforementioned kinematic limtis can be generalized to QCD, providing rich content for theoretical and phenomenological studies, as major process has been achieved in the triple-collinear limit [67][68][69][70].…”
Section: Special Kinematicsmentioning
confidence: 96%
“…In addition to the leading asymptotic behaviours we provide, our result contains information about subleading powers as well. The data in the triple-collinear, squeezed and coplanar limit will shed new light on corresponding OPE limits of the light-ray operators [64], thus making it possible to understand these limits at arbitrary coupling [65,66]. In the meantime, the analysis in each aforementioned kinematic limtis can be generalized to QCD, providing rich content for theoretical and phenomenological studies, as major process has been achieved in the triple-collinear limit [67][68][69][70].…”
Section: Special Kinematicsmentioning
confidence: 96%
“…It was also shown that it can be directly analyzed inside jets at the LHC using CMS Open Data [88]. This is part of a broader program to reformulate the study of jet substructure in terms of energy correlators [86,[89][90][91][92][93][94]. 1 An important part of this program includes the development of techniques to compute energy correlators on charged particles (tracks) [92,[100][101][102][103] to enable the experimental measurement of higher-point correlators.…”
Section: Asymptotic Energy Flow In Collider Experiments Is Characteri...mentioning
confidence: 99%
“…C. More details can be found in Refs. [85,86]. Figure 15: The probabilities of relative error of twist ≤ 4 blocks approximations G block approx q/g for (a) quark jet and (b) gluon jet.…”
Section: Celestial Block Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6.16), and a jet function for the observable v, occurs also in the collinear factorization. Given that for many interesting jet substructures, the corresponding jet functions have already be obtained up to next-to-next-to-next-to-leading order (N 3 LO), see for instance [126][127][128][129][130][131][132][133][134][135][136], this factorization feature can thus be used to dramatically simplify and realize future calculations of the jet substructure distributions in the small-x regime. Last but not the least, the factorized form lays down the foundation for combining the existing parton shower with the CGC calculations, in which one manage to calculate the fully differential cross section within the CGC framework just like what we have presented in this work, and then shower the physical states in vacuum due to the factorization we pointed out.…”
Section: An Alternative Subtraction and The Small-r Limitmentioning
confidence: 99%